Sustaining Otolaryngology Services for the Long Haul during the COVID-19 Pandemic: Experience from a Tertiary Health System. (July 2020) - Tay, Joshua K.; Lim, Wei Sian; Loh, Woei Shyang; Loh, Kwok Seng
The impact of the COVID-19 pandemic has been far-reaching and has profoundly affected the practice of otolaryngology in an unprecedented way. In this commentary, we draw from our experience in the first 90 days of the pandemic and discuss a set of workflow measures, personal protection equipment protocols, and strategic goals that can provide a safe environment for patients and staff to continue managing a significant proportion of patients in the otolaryngology service during the pandemic.